New Dimensions of Adjustment to Globalization - Marialuz Moreno Badia; Veerle Slootmaekers; Ilke Van Beveren (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
Using firm-level data for Estonia for the years 1997-2005, we analyze the impact of international competition on firm dynamics, considering both firm closedown and product switching. This paper contributes to the literature in two important ways: (1) this is the first paper to study the detfirminants of exit and product switching in an emerging market; and (2) we consider explicitly the role of export opportunities. Our results indicate that globalization affects firm closure and product switching differently. In particular, firm exit is positively related to the degree of intra-industry trade while the decision to switch is affected only by the conditions in export markets. This is in sharp contrast to previous findings for industrial countries.
Keywords: D21; D24; F18; L25; L60; 330; Product switching; Exit; International trade; Comparative Advantage; Internationaler Wettbewerb; Globalisierung; Produktpolitik; Diversifikation; Estland